Study Design and Baseline Characteristics of ALIGN, a Randomized Controlled Study of Atrasentan in Patients With IgA Nephropathy - Hiddo J.L. Heerspink; Meg Jardine; Donald E. Kohan; Richard A. Lafayette; Adeera Levin; Adrian Liew; Hong Zhang; Irene Noronha; Hernan Trimarchi; Fan Fan Hou; Ronny Renfurm; Todd Gray; et al. (Kidney International Reports)
Introduction: Endothelin A (ETA) receptor activation is a driver of proteinuria, kidney inflammation, and fibrosis in IgA nephropathy (IgAN). Atrasentan, a selective ETA receptor antagonist, has potential to reduce proteinuria and preserve kidney function in IgAN. ALIGN (NCT04573478) is a phase 3, randomized, double-blind, placebo-controlled clinical trial of atrasentan in patients with IgAN at high risk of kidney function loss. Methods: Eligibility criteria for the ALIGN main stratum included patients with biopsy-proven IgAN, total protein excretion ≥ 1 g/d, estimated glomerular filtration rate (eGFR) ≥ 30 ml/min per 1.73 m2, receiving a maximally tolerated stable dose of a renin-angiotensin system (RAS) inhibitor. An exploratory stratum enrolled participants also receiving a stable dose of sodium glucose cotransporter-2 inhibitors (SGLT2i). Participants were randomized to 0.75 mg atrasentan or placebo orally daily for 132 weeks followed by a 4-week wash-out period. The primary outcome is proteinuria change from baseline (24-hour urine protein-to-creatinine ratio [UPCR]) to week 36 in the main stratum. Key secondary end points include eGFR change from baseline to week 136, safety, and tolerability. Results: Enrolment occurred across 20 countries; 404 patients were randomized: 340 in the main stratum and 64 in the SGLT2i stratum. At baseline in the main stratum, mean age was 44.7 years, 42.4% were female, mean eGFR and median UPCR were 58.9 ml/min per 1.73 m2 and 1.4 g/g, respectively. Conclusion: The ongoing ALIGN trial evaluates the efficacy and safety of atrasentan in a representative global IgAN population at risk for disease progression despite optimized RAS inhibitor therapy and includes an exploratory stratum evaluating atrasentan use in combination with an SGLT2i.